Como mobilizar designers para a questão do envelhecimento e velhice? a relevância de práticas intergeracionais em design - Osmo, Lilian (2018)
This study presents and questions an experiment carried out in the discipline of Ergonomics, which I teach in a Course of Design at a São Paulo university. The concern of the experiment is to awaken in the youngsters - the future designers -, the responsibility to create a design which is more inclusive and more affectionate towards old people. The project selected with this aim consists of the production of an user friendly guide, which teaches the elderly how to use, by themselves, the APP to watch films Netflix. The work investigates whether there is a gain in the quality of the produced guide and in the learning process of ergonomics when the teaching method includes a more humane view on aging, based in great part on the philosophy of encounter of Martin Buber and on exercises experiencing empathy with aging. The general aim of the research is to elaborate a proposal for a teaching method based on the principles of the science of Ergonomics allied with a theoretical analysis of empathy, and guiding the student of design to adopt a posture of respect with the aged and to seek more inclusive and user friendly solutions for products. The evaluation method of the project consisted of reports elaborated by the students after tests of their user guides with the aged people, as well as questionnaires answered by them in class about their impressions on their work and experiences. The result of the experiment shows that, although a more lasting more positive view of the aged by the young had not been achieved, when the latter would see the former as an active, eager to achieve individual it was possible to witness moments of true empathy during the tests of the guides. With the support of humanist thinkers like Buber, we conclude that it is necessary to continue the fight against prejudices ingrained in human beings and that the educator has nowadays a great responsibility to promote in the teaching environment activities originating more humane, more affectionate and more inclusive view on human diversity